2017
DOI: 10.1111/inm.12307
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing oral health for better mental health: Exploring the views of mental health professionals

Abstract: The association between oral health, self‐esteem and quality of life is well established yet there is limited research on the impact of addressing the poor oral health of people living with mental health disorders. Greater consideration is warranted on how enhancing oral health in the course of mental healthcare might reduce the burden of a person's ill health. The role of mental health professionals is important in this regard yet uncertainty persists about the role these providers can and should play in prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…consumers' lack of interest in oral health, staff having insufficient knowledge about oral health and dental services, and lack of time when working with consumers). A qualitative study of Western Australian community mental health workers' views on oral health identified similar barriers to this present study [41]. Our results indicate that CRSWs who rated their oral health knowledge and confidence higher perceived fewer barriers to oral health promotion.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…consumers' lack of interest in oral health, staff having insufficient knowledge about oral health and dental services, and lack of time when working with consumers). A qualitative study of Western Australian community mental health workers' views on oral health identified similar barriers to this present study [41]. Our results indicate that CRSWs who rated their oral health knowledge and confidence higher perceived fewer barriers to oral health promotion.…”
Section: Discussionsupporting
confidence: 69%
“…They recognised that they have a role to play in supporting consumers' oral health and believed oral health promotion should be delivered in community mental health settings. Other studies with health professionals from a range of disciplines also found participants to be supportive of oral health promotion programs targeting the population groups they work with, and indicated the need for appropriate strategies to integrate oral health promotion activities into routine service delivery [28,29,[37][38][39][40][41][42][43][44][45]. There is strong evidence that non-dental professionals (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It indicates elevated vulnerability in our sample that is likely associated with exposure to intersecting clinical and demographic risk factors (10,26). It also warrants further research on strategies to improve oral health among individuals with psychiatric disorders, given that this may lead to improved mental health outcomes (8).…”
Section: Discussionmentioning
confidence: 85%
“…Seeing that oral health is a very important part of wellbeing in patients with mental illnesses, we should focus on providing these patients an integrated and multidisciplinary attention that includes general practitioners, psychiatrists, dentists, psychologists and nutrition professionals. It has been shown that mental health professionals exhibit ambivalence, reluctance and lack of training in raising oral health issues, despite its acknowledged importance, so more adequate training is in order to overcome this treatment obstacle (Scrine et al 2018).…”
Section: The Need For Collaboration and Overcoming The Professional Gap Between Psychiatry And Dentistrymentioning
confidence: 99%